Regulation of signaling events involved in the pathophysiology of neovascular AMD - Wang, Haibo; Hartnett, M Elizabeth (Molecular vision, 2016)
Neovascular age-related macular degeneration (AMD) is a complex disease in which an individual's genetic predisposition is affected by aging and environmental stresses, which trigger signaling pathways involving inflammation, oxidation, and/or angiogenesis in the RPE cells and choroidal endothelial cells (CECs), to lead to vision loss from choroidal neovascularization. Antiangiogenic therapies have greatly improved clinical outcomes in the last decade; however, vision improves in less than half of patients treated for neovascular AMD, and treatments remain inadequate for atrophic AMD. Many studies focus on genetic predisposition or the association of outcomes in trials of human neovascular AMD but are unable to evaluate the effects between different cell types involved in AMD and the signaling events that take place to cause pathologic biologic events. This manuscript complements other reviews in that it describes what is known generally in human AMD studies and clinical trials testing methods to inhibit vascular endothelial growth factor (VEGF inhibitors) and presents pathologic signaling events that develop in two important cell types, the RPE cells and the CECs, when stimulated by stresses or placed into conditions similar to what is currently understood to occur in neovascular AMD. This manuscript complements other reviews by discussing signaling events that are activated by cell-cell or cell-matrix interactions. These considerations are particularly important when considering growth factors, such as VEGF, which are important in physiologic and pathologic processes, or GTPases that are present but active only if GTP bound. In either case, it is essential to understand the role of signaling activation to distinguish what is pathologic from what is physiologic. Particularly important is the essential role of activated Rac1 in CEC transmigration of the RPE monolayer, an important step in blindness associated with neovascular AMD. Other concepts discussed include the importance of feed-forward loops that overwhelm mechanisms that seek to restore homeostasis in cells and the importance of regulating, instead of abolishing, signaling events in a chronic, complex disease, such as neovascular AMD. These concepts are important as we move to the next stages in developing treatments for neovascular AMD. A novel therapeutic strategy that will be discussed is activating an isoform of the GTPase, Rap1, which can regulate downstream signaling and a pathologic feed-forward loop leading to Rac1 activation and migration of CECs.